FIELD EXPERIMENT: FODDER MAIZE AND STYLO (1:1) INTERCROPPING IN ODISHA’S MID-CENTRAL TABLE LAND ZONE - D.A, Morrow (International Journal of Allied Sciences (IJAS), 2022)
Uterine torsion is a rare but serious condition in goats that can lead to maternal and fetal complications if not managed in a timely and appropriate manner. This case study presents a successful management of uterine torsion in a 2-year-old Kodi Aadu goat using the modified Schaffer’s method. The doe had shown symptoms of abdominal straining and dullness, and upon examination, a post cervical right side torsion was diagnosed. The torsion was corrected using the modified Schaffer’s method, and the doe was treated with various medicines and supportive therapies. A live female kid was delivered successfully by simple traction per-vaginally. The study suggests that the modified Schaffer’s method could be used for correction of post-cervical uterine torsion in goats. The importance of timely intervention and appropriate treatment in managing uterine torsion to avoid maternal and fetal complications is highlighted.